1999
DOI: 10.4269/ajtmh.1999.60.767
|View full text |Cite
|
Sign up to set email alerts
|

Differential perpetuation of malaria species among Amazonian Yanomami Amerindians.

Abstract: Abstract. To determine whether malaria perpetuates within isolated Amerindian villages in the Venezuelan Amazon, we surveyed malaria infection and disease among 1,311 Yanomami in three communities during a 16-month period. Plasmodium vivax was generally present in each of these small, isolated villages; asymptomatic infection was frequent, and clinical disease was most evident among children less than five years of age (odds ratio [OR] ϭ 6.3, 95% confidence interval [CI] ϭ 1.4-29.2) and among persons experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
2
18
0
2
Order By: Relevance
“…32,33 However, absence of symptoms in a sectional study is not tantamount to asymptomatic malaria, which can only be ascertained through follow-up protocols. Studies carried out in Papua New Guinea and Thailand have clearly shown the existence of asymptomatic Plasmodium infections out of Africa.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 However, absence of symptoms in a sectional study is not tantamount to asymptomatic malaria, which can only be ascertained through follow-up protocols. Studies carried out in Papua New Guinea and Thailand have clearly shown the existence of asymptomatic Plasmodium infections out of Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Antimalarial immunity can suppress gametocytemia (Baird et al 1991), and therefore reduce malaria transmission, and control parasitemia (Bull & Marsh 2002), leading to a reduction in malaria morbidity. It can be assumed that the relative isolation of Yanomami villagers (Laserson et al 1999) restricted the variety of circulating isolates of malaria parasites (Maitland et al 2000) and contributed to the efficacy of immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies carried out in Brazil (Jones & Neto 1971Prata et al 1988, Andrade 2001a,b, Pithan et al 2002, Scopel et al 2005 and in other Latin American countries (Gonzalez 1997, Pérez 1998, Laserson et al 1999, Suárez-Mutis et al 2000a,b, Roper et al 2000, Roshnavaran et al 2003, Branch et al 2005 were important for the global comprehension of the problem.…”
Section: Chronicity and Asymptomatic Infectionmentioning
confidence: 95%
“…P. vivax was found in 74.7% of the infections, P. falciparum in 26.6%, including mixed infection in 1.6%, and P. malariae in 0.3%. IgG antibodies for P. vivax and P. falciparum were detected by indirect immunofluorescence in 83.2 and 71.7%, respectively, but the geometrical means of the assays were low (72.5 and 54.6), thus characterizing unstable transmission.Other studies carried out in Brazil (Jones & Neto 1971Prata et al 1988, Andrade 2001a,b, Pithan et al 2002, Scopel et al 2005 and in other Latin American countries (Gonzalez 1997, Pérez 1998, Laserson et al 1999, Suárez-Mutis et al 2000a,b, Roper et al 2000, Roshnavaran et al 2003, Branch et al 2005 were important for the global comprehension of the problem. …”
mentioning
confidence: 95%